Analysis of The Impact of Hardware And Software System Develop-ments And Inte-gration On The Domestic Healthcare Market - Yakhshiboyev R.E. Yakhshiboyev R.E. (Green Publisher Indonesia, 2024)
This article examines the profound impact of advanced hardware and software system developments and their integration in transforming the domestic healthcare sector. It explores how these technological advancements are reshaping healthcare delivery, improving patient outcomes, and contributing to the efficiency of healthcare services.